1998
DOI: 10.3109/10731199809119772
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Based Oxygen Carriers: How Much Methemoglobin is too Much?

Abstract: The oxidized form of hemoglobin, methemoglobin, is unable to deliver oxygen to tissues. Hemoglobin based oxygen carriers generally lack the natural oxidative-reductive machinery present within the red blood cell that converts methemoglobin to hemoglobin. This study examines tolerable levels of methemoglobin that can be present in solutions of polyethylene glycol (PEG) conjugated bovine hemoglobin without compromising its ability to deliver oxygen. Rodents were exchange-transfused to 30% of their estimated bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
59
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 22 publications
7
59
0
1
Order By: Relevance
“…Our data are in agreement with several studies using large-volume HBOC administration that documented significant ferric Hb formation in sheep (Lee et al, 1995), rabbits (Dunne et al, 2006), andhumans (O'Hara et al, 2001). In addition, administration of various percentages of oxidized PEGylated-Hb to rats as a 30% ET demonstrated that excess of 10% PEGylated-Hb in the oxidized form (ferric PEGylated-Hb) reduced both kidney and liver oxygen tension (Linberg et al, 1998). These observations suggest a potential for increased toxicity as a result of diminished oxygen delivery and oxidative side reactions caused by excessive ferric HBOC exposure.…”
Section: Discussionmentioning
confidence: 79%
“…Our data are in agreement with several studies using large-volume HBOC administration that documented significant ferric Hb formation in sheep (Lee et al, 1995), rabbits (Dunne et al, 2006), andhumans (O'Hara et al, 2001). In addition, administration of various percentages of oxidized PEGylated-Hb to rats as a 30% ET demonstrated that excess of 10% PEGylated-Hb in the oxidized form (ferric PEGylated-Hb) reduced both kidney and liver oxygen tension (Linberg et al, 1998). These observations suggest a potential for increased toxicity as a result of diminished oxygen delivery and oxidative side reactions caused by excessive ferric HBOC exposure.…”
Section: Discussionmentioning
confidence: 79%
“…The circulating levels of MetHb were increased from 3 to 40% in the first 24 h of infusion of the HBOC. The question of how much MetHb is too much was recently addressed in a rat model of 30% exchange transfusion of conjugated Hb with polyethylene glycol (PEG-Hb) (36). It was estimated that MetHb levels greater than 10% significantly decrease the ability of this Hb to oxygenate tissues.…”
Section: Discussionmentioning
confidence: 99%
“…We seek to synthesize acellular bovine HBOCs (bHBOCs) that improve tissue pO 2 , maintain the mean arterial pO 2 , and target O 2 delivery to low pO 2 tissues. We are focused on synthesizing acellular bHBOCs with the following design criteria: high O 2 affinity; methemoglobin (metHb) level <10%; numberaveraged molecular weight greater than that of bovine hemoglobin (bHb) (Linberg et al, 1998;Reid, 2003;Tsai et al, 2003;Winslow, 2003); and reduced cooperativities (Kavdia et al, 2002). This work describes the synthesis and characterization of polymerized bHBOCs derived from novel cross-linking agents for potential application in treating patients suffering from stroke or hemorrhagic shock.…”
Section: Introductionmentioning
confidence: 99%